Effects of anaerobic fatigue induced by sport-specific exercise on postural control in highly-trained adolescent road cyclists - Zajac, B.; Mika, A.; Gaj, P. K.; Ambrozy, T. (Applied Sciences, 2023)
The aim of this study was to evaluate whether and how anaerobic fatigue induced by sport-specific exercise affects the postural control of highly-trained adolescent road cyclists. Twenty-three male athletes, aged 15-18 years, were included in the study. Postural control was assessed using the pedobarographic platform (bipedal upright stance, sequentially, with eyes open (EO) and closed (EC) for 60 s each, with a 30 s interval), before and 3 min after a 30 s all-out effort performed on the ergometer. The results showed significant increases in the 95%-confidence ellipse area (p-value 0.000 and 0.001 for EO and EC, respectively), as well as centre-of-pressure (CoP) range displacement in the anteroposterior (p-value 0.000 for both EO and EC) and mediolateral (p-value 0.011 and 0.001 for EO and EC, respectively) planes. In addition, a significant decrease in CoP mean sway frequency was observed (p-value 0.000 and 0.001 for EO and EC, respectively), but no changes were noted in CoP mean velocity (p-value 0.316 and 0.670 for EO and EC, respectively). In our study, it has been indicated that anaerobic fatigue induced by sport-specific exercise deteriorates postural control in adolescent cyclists. Moreover, cycling training may affect the quality of postural corrective reactions occurring in response to anaerobic fatigue.